THE CONTRIBUTION OF SEVENTH DAY ADVENTIST TRANSNATIONAL ORGANIZATIONS IN BUILDING GLOBAL PEACE THROUGH TOLERANCE: A CASE STUDY IN INDONESIA - Christy Damayanti; Setyasih Harini; Sritami Hatmini; Hasna Wijayati (Bajang Institute, 2022)
Seventh day Adventist, as a religion-based transnational organization, have the potential to support global peace building. Seventh day Adventist exist in various countries in the world, including in Indonesia, as one of the plural countries that officially recognizes Christianity. This study aims to analyze the contribution of Seventh day Adventist transnational organizations to building global peace through tolerance by using case studies in Indonesia as the focus of research. This research is qualitative in nature with an intrinsic case study method. Data was collected using in-depth interviews, observation, and document studies. Informan include Seventh day Adventist regional church leaders, women administrators, Youth Ministries, Pathfinders, Adventists, other religious leaders, and non-adventist communities to support the triangulation of informan. The analysis is supported by the theory of neoliberalism and Huntington's clash of civilizations. The study found that the contribution of the Seventh day Adventist can be seen through a global identity that is firmly structured and consistent so that it is able to build and strengthen the value of tolerance of its members in various countries, which in turn encourages the building of global peace. As a religious-based transnational organization, Seventh day Adventist in Indonesia has activities that are consistent with a clear line of coordination from the regional to the international level. This is able to influence the values held by its members. In this way, these transnational organizations contribute to the quality of global peace.